Délocalisations : de quoi parle-t-on ?De la quantification des opérations à la qualification des processus - Christophe Carrincazeaux; Marie Coris; Alain Piveteau (Revue de la Régulation)
Relocations are usually interpreted as part of economic globalisation. Recent qualitative trends give a new picture of relocations and put into question our usual understanding of the phenomena. “Relocations: what are we talking about” goes back to the definition and quantification of relocations and proposes to interpret these new trends through firms’ mobility and the rationality of their location choices. We finally discuss some analytical ways of understanding and explaining what is at stake in the relocation process at the firm and industry level.